Tuning the Aggregation of N^N^C Pt(II) Complexes by Varying the Aliphatic Side Chain and Auxiliary Halide Ligand: 1H and 195Pt NMR Investigation. Issue 38 (14th October 2019) - Evstigneev, Maxim P.; Lantushenko, Anastasiya O.; Yakovleva, Yulia A.; Suleymanova, Alfiya F.; Eltsov, Oleg S.; Kozhevnikov, Valery N.
Abstract : A series of six tridentate cyclometallated N ^ N ^ C Pt(II) complexes with different halide auxiliary ligands and different aliphatic side chains have been prepared. All complexes show concentration‐dependent NMR spectra. Their self‐association was studied by a dilution method monitoring both the 1 H as well as 195 Pt nuclei. Both techniques show similar results validating that 195 Pt NMR is an important methodology to study self‐association of potentially any Pt complex regardless of the nature of the ligands. Experimental data allowed to predict the most probable geometry of the dimers and to get insight into the structural and thermodynamic specificity of the aggregation. The in‐depth analysis of the data suggests that the halide auxiliary ligand has no significant influence on self‐association while the effect of the aliphatic side chain depends on the length and the structure of the chain. Abstract : A series of three complexes with identical tridentate N ^ N ^ C cyclometallating ligand but different halide auxiliary ligands have been prepared, and their self‐association was studied by dilution method monitoring both the 1 H as well as 195 Pt nuclei.